1988
DOI: 10.1007/bf00417265
|View full text |Cite
|
Sign up to set email alerts
|

Isometric and isokinetic muscle strength, anthropometry and physical activity in 8 and 13 year old Swedish children

Abstract: Isometric muscle strength of the hand-grip and of trunk flexion and extension, and isokinetic torque of elbow and knee flexion and knee extension were assessed in a random sample of 8 and 13 year old Swedish children. The results were compared with respect to sex and age in absolute terms and relative to weight, height2 and estimates of lean body mass and cross-sectional muscle area. Daily physical activity was also estimated. The muscle strength variables were in general found to be very similar in the 8 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 14 publications
6
43
3
Order By: Relevance
“…Despite this, the NC group recorded similar results to those in the study of Sunnegardh and coworkers (1988) for the isometric extensor torque, while the peak torque produced under isokinetic conditions was in some cases slightly more (Horvat et al 1999) and some cases slightly less (Sunnegardh et al 1988) than that previously reported under similar conditions. A measure that is often derived from the peak extensor and flexor torque to provide information about the muscular imbalance around a joint is the flexor-extensor percentage, where the peak flexor torque is expressed as a percentage of the peak extensor torque.…”
Section: Discussioncontrasting
confidence: 29%
See 2 more Smart Citations
“…Despite this, the NC group recorded similar results to those in the study of Sunnegardh and coworkers (1988) for the isometric extensor torque, while the peak torque produced under isokinetic conditions was in some cases slightly more (Horvat et al 1999) and some cases slightly less (Sunnegardh et al 1988) than that previously reported under similar conditions. A measure that is often derived from the peak extensor and flexor torque to provide information about the muscular imbalance around a joint is the flexor-extensor percentage, where the peak flexor torque is expressed as a percentage of the peak extensor torque.…”
Section: Discussioncontrasting
confidence: 29%
“…Burnie and Brodie 1986, Sunnegardh et al 1988, Henderson et al 1993) and adults (e.g. Ewing et al 1990, Hall andRoofner 1991), peak torque decreased with increasing velocity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puberty is the period of transition from childhood to adulthood with sexual maturation and includes changes in the nervous and endocrine systems and the corresponding anthropometric, physiological and psychological changes [9][10][11]. During and after puberty, a marked increase in physical performance occurs as a result of muscular, neuronal, hormonal and biomechanical factors [12].…”
Section: Introductionmentioning
confidence: 99%
“…A single study (Luk et al 2003) has shown a weak correlation between height with lifting capacity. Studies dealing with the influence of height on trunk strength have often focused on growing adolescents (Sinaki et al 1996;Sunnegardh et al 1988). We conclude that height is a strong factor influencing lifting capacity but the causality of this phenomenon is difficult to explain.…”
Section: Discussionmentioning
confidence: 86%